Speech Enhancement Based on the Multi-Scales and Multi-Thresholds of the Auditory Perception Wavelet Transform - TAO, Zhi; ZHAO, He-Ming; ZHANG, Xiao-Jun; WU, Di (Archives of Acoustics, 2011)
This paper proposes a speech enhancement method using the multi-scales andmulti-thresholds of the auditory perception wavelet transform, which is suitable fora low SNR (signal to noise ratio) environment. This method achieves the goal of noisereduction according to the threshold processing of the human ear’s auditory maskingeffect on the auditory perception wavelet transform parameters of a speech signal.At the same time, in order to prevent high frequency loss during the process of noisesuppression, we first make a voicing decision based on the speech signals. Afterwards,we process the unvoiced sound segment and the voiced sound segment according tothe different thresholds and different judgments. Lastly, we perform objective andsubjective tests on the enhanced speech. The results show that, compared to otherspectral subtractions, our method keeps the components of unvoiced sound intact,while it suppresses the residual noise and the background noise. Thus, the enhancedspeech has better clarity and intelligibility.